Low‐contrast visual acuity versus low‐luminance visual acuity in choroideremia - Wood, L; Jolly, J; Andrews, C; Wilson, I; Hickey, D; Kapetanovic, J; Maclaren, R (Wiley, 2020)
Clinical relevance Choroideremia is a progressive X‐linked inherited rod‐cone dystrophy. Patients present with nyctalopia and progressive visual field loss, but visual acuity remains well preserved early on. This study showed that low‐luminance visual acuity may be a useful clinical outcome measure during earlier disease stages.